Analysis of fringing electric field sensor sensitivity based on its geometry shape and sizing / Khairul Razman Mohd Razali - Mohd Razali, Khairul Razman (2013)
The purpose of this project is to analyze the ‘Fringe Electric Field (FEF) Sensor’ sensitivity by varying it geometry shape and electrode size. Fringing electric field (FEF) sensors are used to determine the properties that cannot be measured directly for example electrostatic, temperature, hardness and many others. In this project, the FEF sensor is used to determine the moisture level in soil by measuring its capacitance values. It starts with simulation using Finite Element Method Magnetic (FEMM) to simulate the FEF sensor. The process then continues with fabricating the FEF sensor using Printed Circuit Board (PCB) technology. The FEF sensor will be tested using LCR meter to measure the capacitance values and the data obtained are varied by the geometry shape, electrode width and number of electrode of the FEF sensor. The results obtained proved that the geometry shape and sizing can improve the sensitivity of the FEF sensor.